PERKAWINAN SEKUFU DALAM PERSPEKTIF HUKUM ISLAM: (Studi Kasus di Daerah Napradu Provinsi Pattani Thailand Selatan) - Hussam Duramae (Fakultas Syariah Institut Agama Islam Negeri Palu, 2018)
Kafa’ah or kufu’ in marriage became a polemic among the laity. This study aims to find out how marriage sekufu in Islamic perspective in the area of ​​Napradu Pattani Province, Southern Thailand. The data were obtained by interviewing Imam - Imam, bilal or preacher mosque in Napradu. From the analysis of interview results, found 3 main ones in the concept of kafa'ah, they are religion, degree / nasab, and work / profession. The balance for starting a family should be the match between couples. It became a perception for the people of Napradu to reach a harmonious family. Forms of marriage implementation sekufu in Napradu region must follow syafi'i Mazhab. Therefore there are several indicators that must be met, namely; a) the male partner asks the parent to seek a spouse or ask to see the woman he wants, intent to align the parents' appetite with the child; b) a bridgehead between the prospective husband's family and the prospective wife's family on the matter of marriage; c) a suitable and equivalent female candidate to a potential male partner.